2019
DOI: 10.1016/j.quascirev.2019.105863
|View full text |Cite
|
Sign up to set email alerts
|

Climatic reconstruction for the Younger Dryas/Early Holocene transition and the Little Ice Age based on paleo-extents of Argentière glacier (French Alps)

Abstract: Investigation of Holocene extents of mountain glaciers along with the related naturally-driven climate conditions helps improve our understanding of glacier sensitivity to ongoing climate change. Here, we present the first Holocene glacial chronology in the Mont-Blanc massif (Argentière glacier) in the French Alps, based on 25 in situ-produced cosmogenic 10 Be dates of moraines and glacial bedrocks. The obtained ages from mapped sequences of moraines at three locations reveal that the glacier was retreating fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 60 publications
7
49
1
1
Order By: Relevance
“…4D; Table DR2). These results agree with known deglaciation scenarios for the Alps (Ivy-Ochs, 2015; Wirsig et al, 2016;Protin et al, 2019). Indeed, ice-surface lowering starting at 16.6 ± 0.6 ka at an elevation of 2550 masl coincides with TCN dating from the southern side of the Mont Blanc massif (Wirsig et al, 2016).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…4D; Table DR2). These results agree with known deglaciation scenarios for the Alps (Ivy-Ochs, 2015; Wirsig et al, 2016;Protin et al, 2019). Indeed, ice-surface lowering starting at 16.6 ± 0.6 ka at an elevation of 2550 masl coincides with TCN dating from the southern side of the Mont Blanc massif (Wirsig et al, 2016).…”
Section: Resultssupporting
confidence: 88%
“…Using modern records, a rock surface at 1800 masl spends 8% of the year in the FCW (−3 °C to −8 °C; Matsuoka and Murton, 2008), or 14% and 21% at 2400 and 3200 masl, respectively. This trend also holds for the Younger Dryasearly Holocene transition, assuming the temperature was 4.5 °C less than today (3.6-5.5 °C, Protin et al, 2019) and that the summer-winter difference was similar to today. The observed decrease in erosion rates with elevation is also too pronounced to be explained by chemical weathering alone.…”
Section: Resultsmentioning
confidence: 60%
“…Glaciers are still present at high altitude in the Mont Blanc Massif. The mapping and dating of moraines in this area indicate that deglaciation took place in several steps during the Late Glacial (Coutterand and Nicoud, 2005;Protin et al, 2019).…”
Section: Methods and Site Choicementioning
confidence: 99%
“…Several examples of this complexity have been observed for past glacial valleys in the Alps and in the Pyrenees (Fabel et al, ; Delmas et al, ; Chenet et al, ; Protin et al, ). Erratic boulders with exposure cosmogenic ages from the last glacial period lie on older polished surfaces (Delmas et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This LIA extent on the southern slopes of the Central Pyrenean cirques may correspond to the maximum glacier advance during the Holocene (Palacios et al 2017) as recently documented in the Maladeta massif (Crest et al 2017). This contrasts with several places in the Alps (Schimmelpfennig et al 2012(Schimmelpfennig et al , 2014Solomina et al 2015;Protin et al 2019) where an early Holocene period leads to observed glacier advance larger than that of the LIA.…”
Section: Introductionmentioning
confidence: 52%